2002
DOI: 10.1590/s1413-86702002000500004
|View full text |Cite
|
Sign up to set email alerts
|

Estimated prevalence of immunity to poliomyelitis in the city of São Paulo, Brazil: a population-based survey

Abstract: Objectives. Estimate the prevalence of immunity to poliomyelitis (anti-polio antibodies) in the city of São Paulo/Brazil through a population-based survey. Methods. A quantitative and inductive method was used to draw a representative sample of the population. Randomization and stratification (based on sex, age and residence region) was done, and 1,059 individuals were studied on a home-visit basis (structured questionnaires and blood samples). A microneutralization test was performed to detect anti-polio anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
1
1
1
Order By: Relevance
“…The increasing seroprevalence to PV1 and PV3 with age in our study, as has been seen elsewhere [21,22], likely reflects increased remote exposure to circulating WPV types 1 and 3 in older persons in our population and a greater opportunity for exposure to shed polio vaccine virus through contact with children. Although we did not measure susceptibility in men, previous studies have demonstrated lower PV antibody seropositivity in men than women [23][24][25][26], suggesting the overall level of immunity in the adult population might be even lower than in our survey. Current immunity to polio in women in our survey is less than the population immunity documented prior to recent outbreaks in Tajikistan and China [10,27].…”
Section: Discussioncontrasting
confidence: 56%
“…The increasing seroprevalence to PV1 and PV3 with age in our study, as has been seen elsewhere [21,22], likely reflects increased remote exposure to circulating WPV types 1 and 3 in older persons in our population and a greater opportunity for exposure to shed polio vaccine virus through contact with children. Although we did not measure susceptibility in men, previous studies have demonstrated lower PV antibody seropositivity in men than women [23][24][25][26], suggesting the overall level of immunity in the adult population might be even lower than in our survey. Current immunity to polio in women in our survey is less than the population immunity documented prior to recent outbreaks in Tajikistan and China [10,27].…”
Section: Discussioncontrasting
confidence: 56%
“…In the final step of polio eradication, seroprevalence studies have increased in importance and can point to immune gaps in specific populations. 4 , 5 , 6 Serum neutralizing antibody titers, the traditional measure of vaccine-induced immunity, have a reliable correlation with protection against paralytic poliomyelitis. However, it is a limited determinant of virus replication in the intestinal tract.…”
mentioning
confidence: 99%
“…Στη μελέτη των Viviano και συν., το γεωγραφικό διαμέρισμα προέλευσης δεν φάνηκε να σχετίζεται με την ορολογική προστασία, το μέγεθος όμως του δείγματος ήταν μικρότερο και άλλης σύνθεσης από την παρούσα μελέτη, αντίθετα με τη μελέτη των Van Schaik και συν., όπου η αναλογία του πληθυσμού, το μέγεθος του δείγματος και τα ευρήματα ήταν παρόμοια με τα δικά μας170,171 . τίτλου αντισωμάτων172,174,175 . Θα πρέπει να σημειωθεί ότι, σημαντικό ρόλο για την ορολογική προστασία διαδραματίζει, το εμβολιαστικό σχήμα, το είδος του χρησιμοποιούμενου εμβολίου, καθώς και ο τρόπος συντήρησης και εφαρμογής του173,174,176,177 .…”
unclassified